Assessment of intake of iron and nutrients that affect bioavailability of daily food rations of girls - Anna Broniecka; Joanna Wyka; Monika Bronkowska; Ewa Piotrowska; Jadwiga Biernat (Annals of Agricultural and Environmental Medicine, 2014)
INTRODUCTION AND AIM In a human body iron occurs at a level of 3 to 5 g, 60-70 % of which are in hemoglobin, ca. 10% in myoglobin, and ca. 3% are accumulated in enzymes of cellular respiration or enzymes degrading toxic hydrogen peroxide. The other part of iron is accumulated in liver, spleen, kidneys and bone marrow. The dietary deficiency of iron appears at its insufficient level in a diet and at impaired absorption of iron ions present in food products by a body. Groups at an especially high risk of iron deficiencies include, among others, menstruating girls in the pubescence period and women with heavy and irregular menstruations, as well as vegetarians and patients with chronic enteritis. The aim of this study was to evaluate the intake of iron and nutrients that affect its bioavailability from daily food rations of girls. MATERIAL AND METHODS The study included 159 girls aged 17-18, students of high schools in the city of Wroclaw. The study was conducted between November 2010 and ay 2011. Girls were divided into 3 subgroups according to the BMI score. Girls’ diets were analyzed with the method of a direct interview of the last 24 hours before the test and the interview was repeated seven times. RESULTS The present study demonstrated that the intake of iron from food rations of almost all the girls surveyed was below the requirements defined for this age group. Statistically significant differences were noted in the intake of energy and nutrients among the three distinguished subgroups of girls. CONCLUSIONS Food rations of the surveyed girls were characterized by a low, compared to dietary allowances, calorific value, which resulted in deficiencies of nutrients increasing iron bioavailability.